Influence of TiO2 nanotube morphology and TiCl4 treatment on the charge transfer in dye-sensitized solar cells - Lee, Sun Hong; Chae, Sang Youn; Hwang, Yun Jeong; Koo, Kee-Kahb; Joo, Oh-Shim (SPRINGER, 2013)
Dye-sensitized solar cells (DSSCs) were fabricated using TiO2 nanoparticles (NPs), TiO2 nanotube arrays (NTAs), and surface-modified NTAs with a TiCl4 treatment. The photovoltaic efficiencies of the DSSCs using TiO2 NP, NTA, and TiCl4-treated NTA electrodes are 4.25, 4.74, and 7.47 %, respectively. The highest performance was observed with a TiCl4-treated TiO2 NTA photoanode, although in the case of the latter two electrodes, the amounts of N719 dye adsorbed were similar and 68 % of that of the NP electrode. Electrochemical impedance measurements show that the overall resistance, including the charge-transfer resistance, was smaller with NTA morphologies than with NP morphologies. We suggest that a different electron transfer mechanism along the one-dimensional nanostructure of the TiO2 NTAs contributes to the smaller charge-transfer resistance, resulting in a higher short circuit current (J (sc)), even at lower dye adsorption. Furthermore, the TiCl4-treated NTAs showed even smaller charge-transfer resistance, resulting in the highest J (sc) value, because the downward shift in the conduction band edge improves the electron injection efficiency from the excited dye into the TiCl4-treated TiO2 electrodes.
Keywords: NANOPOROUS TIO2; RECOMBINATION; ELECTRODES; FILMS; PHOTOCARRIERS; REPLACEMENT; TITANIA; CO